Prenatal sonographic delineation of the complex cardiac anatomy of thoraco-omphalopagus twins - T. Tongsong (2018)
We describe a case of thoraco-omphalopagus twins diagnosed at 18 weeks' gestation. Each twin had a separate set of anatomical structures except for a shared heart, upper liver and anterior chest wall. The heart was located at the center of the juncture, and consisted of three atria and two ventricles, each twin having a single ventricle and right atrium but a fused left atrium. A set of great arteries originated from each single ventricle and there was juxtaposition of the aortic and pulmonary values. One twin had transposition of the great arteries, whereas in the other these were normal in configuration. There was only one umbilical cord which contained four vessels (two arteries and two veins). This case report demonstrates the possibility of using fetal echocardiography to delineate the cardiovascular complex of the conjoined heart. Copyright © 2004 ISUOG.